Upaya Pencegahan Penyalahgunaan Narkotika di Kalangan Remaja : Strategi Edukasi, Pengawasan, dan Dukungan - Muhammad Reuben Marcello; Zainudin Hasan (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to analyze the factors that cause teenagers to become involved in narcotics abuse, as well as focus on prevention efforts that can be implemented. Data collection was carried out through document study, observation and interviews. The research results show that narcotics abuse among teenagers is influenced by the social environment, family problems and economic pressure. To prevent this, various efforts have been made, such as intensive education about the dangers of drugs in schools, increasing parental supervision, and strengthening the role of the community. BNN also plays an important role in implementing prevention programs, including outreach, awareness campaigns, and developing a drug-free environment for teenagers. A juridical approach and involvement of various parties is needed so that these prevention efforts can be effective and sustainable.